Financial Technology Company's Debt Collection Method: A Legal Aspect - Suwinto Johan (Universitas Negeri Semarang, 2022)
Online loans are an alternative source of loans for the public. Online lending has grown rapidly. Financial technology companies are online loan providers. Financial technology companies use various ways to collect loans that are not paid by customers when they are due. One of the debt collection methods is to distribute photos and debt collection stories of the customer to the contacts in the customer's mobile number. This distribution has caused unrest for the people contacted either via messenger or via SMS. This research aims to discuss the pattern of debt collection by financial technology companies from a juridical viewpoint. This research uses the juridical normative method. This research concludes that data retrieval and data dissemination constitute a violation of personal data protection for customers and people who receive news and SMS. Retrieval of data without approval or contacting a loan with another party without prior knowledge has violated the personal domain of the data owner. The government needs to immediately issue regulations regarding the protection of personal data related to electronic transactions.